ASSOCIATION BETWEEN NON-DIPPER OR NIGHT-TIME BLOOD PRESSURE PATTERN AND ALCOHOL DRINKING OR QUALITY OF SLEEP IN KOREAN REGISTRY OF AMBULATORY BLOOD PRESSURE MONITORING STUDY. (June 2022) - Shin, Jinho; Kim, Ju-Han; Kim, Woo-Shik; Lee, Sang-Jae; Kim, Jang-Young; Park, Sungha; Lee, Eun-Mi; Ihm, Sang-Hyun; Pyun, Wook Bum
Abstract : Objective: Non-dipper or reverse dipper is known to be associated with adverse cardiovascular prognosis in general population and clinical cohort. There are few large sized to explore the factor related to non-dipper or nighttime blood pressure pattern in terms of sleep quality and lifestyle factors. Design and method: With the database of Korean multicenter nationwide prospective Registry of Ambulatory Blood Pressure monitoring (KORABP) study, 3745 patients referred for blood pressure evaluation was nalysed for clinical profiles including current smoking and alcohol drinking habits, sleep quality in 4 Likert scale as hardly sleep, poor sleep, not so bad, and very good with 1 to 4 points, and medical history. Results: Age was 55.5+/-14.3 years and female was 45%. BMI was 24.7+/-3.4 kg/m2. 33.6% of the study population. Smoking and drinking habits 14.6% and 37.2%, respectively. Prevalence of diabetes mellitus, hypercholesterolemia, and cardiovascular diseases were 19.0%, 27.9% and 22.1%, respectively. Normotensive, untreated hypertension, and treated hypertension were 29.1%, 37.2% and 33.6%, respectively. Sleep qualities in hardly sleep, poor sleep, not so bad, and very good were 14.7%, 32.6%, 32.1% and 20.6%, respectively. In multivariable regression analyses for non-dipper or reverse dipper, age > 56 years, cardiovascular disease history, hypertension by ABPM, and poor sleep are positively associated factors whereas drinking and hypertension by clinic BP were negatively associated factors. Antihypertensive medication has no association. Sleep quality was negatively and positively associated with extreme dipper and reverse dipper, respectively. Conclusions: Age, cardiovascular diseases, and hypertension by ABPM were associated with non-dipper. Drinking was associated with dipper. Good and poor sleep qualities were significant factors for extreme dipper and reverse dipper or non-dipper, respectively.